The interaction between daughterless and Sex-lethal in triploids: A lethal sex-transforming maternal effect linking sex determination and dosage compensation in Drosophila melanogaster. - Cline, T.W. (Developmental Biology, 1983)
Regulation of Drosophila sex determination and X-chromosome dosage compensation in response to the X-chromosome/autosome (X/A) balance of the zygote is shown to require proper functioning of both the da+ gene in the mother and the Sxl+ gene in the zygote. Previous studies led to the hypothesis that zygotic Sxl+ alleles are differentially active in females (XXAA) vs males (XYAA) in response to the X/A balance, and that maternal da+ gene product acts as a positive regulator in this connection. Sxl+ activity was proposed to impose the female developmental sequence on cells which would follow the male sequence in its absence. Important predictions of this proposal are verified. This study focuses primarily on the phenotype of triploid intersexes (XXAAA, X/A = 0.67). They are shown here to survive effects of da and Sxl mutations that would be lethal to diploids. The ambiguous X/A signal of intersexes normally causes them to develop as phenotypic mosaics of male and female tissue. Loss of maternal da+ or zygotic Sxl+ gene function shifts their somatic sexual phenotype to the male alternative. A gain-of-function mutation at Sxl has the opposite effect, imposing female development regardless of the maternal genotype with respect to da. It also reduces their rate of X-linked gene expression. The effects of a duplication of Sxl+ resemble those of the constitutive Sxl allele, but are less extreme. The role of these genes in the process of X-chromosome dosage compensation is inferred indirectly from the strict dependence of the mutations' lethal effects on the X/A balance in haploids, diploids, and triploids, and more directly from the effects of the mutations on the phenotypes of the X-linked neomorphic mutations, Bar and Hairy-wing. The relationship of da+ and Sxl+ gene functions to those of other sex-specific lethal loci in D. melanogaster, and to sex determination mechanisms in other species, is discussed.